Sebutir Pemahaman Teoritis untuk Apresiasi - Ahmadi, Mukhsin, Drs. (citeus, 1981)
This paper discusses the theoretical understanding of tone in literary works, with a particular focus on Herman Melville’s novel Moby Dick. Drawing on E.M. Forster’s framework, especially the concept of prophetic song, the author highlights how tone in literature can reflect the moral condition of humanity and its struggle with nature. Tone is understood not merely as a form of entertainment but as a means of expressing profound universal values. By comparing Forster’s ideas with other literary works, this paper emphasizes the importance of literary appreciation through the recognition and understanding of tone.